VD_FINDINFO HC / 2017 / 1125 vom 18. Dezember 2017 - VD Tribunal cantonal (2017)
ACTION EN DIVORCE, LIQUIDATION DU RÉGIME MATRIMONIAL, COPROPRIÉTÉ, IMMEUBLE | 124b al. 1 CC, 124b al. 2 CC, 205 al. 2 CC, 283 CPC (CH)